Elampus spina - Paukkunen, Juho; Rosa, Paolo; Soon, Villu; Johansson, Niklas; Ødegaard, Frode (Zenodo, 2014)
4. Elampus spina (Lepeletier de Saint Fargeau, 1806) Hedychrum spinus Lepeletier de Saint Fargeau 1806: 121. Holotype ♂; France: Meudon (MSNT) (examined). Elampus productus Dahlbom 1854: 44. Syntypes; Portugal, France (ZMUL). Remarks. This species has been confused with Elampus constrictus in older literature. Sahlberg (1910: 99) and Hellén (1920: 206) reported the species from Finland and Russian Fennoscandia, and Borries (1891: 92) reported it from Denmark (as Notozus productus ). It was at first reported from Sweden by Thomson (1870: 103, as E. productus ), after which it was mentioned by Mocsáry (1889: 68, as Ellampus spina ), Aurivillius (1911: 6) and Jansson (1922: 33, as Notozus spina 1934: 287, as Notozus panzeri var. spina ). All Finnish and Russian Fennoscandian specimens have been checked and found to belong to E. constrictus . It is most likely that also all the Danish and Swedish published records refer to E. constrictus . Rosa & Soon (2012) reported E. spina from Sweden based on an old Swedish specimen deposited in NRM. The specimen was later found to represent a large individual of E. foveatus . Apparently E. spina is a predominantly South European and West Asian species, with some scattered records from central Europe (Banaszak 1980). Published as part of Paukkunen, Juho, Rosa, Paolo, Soon, Villu, Johansson, Niklas & Ødegaard, Frode, 2014, Faunistic review of the cuckoo wasps of Fennoscandia, Denmark and the Baltic countries (Hymenoptera: Chrysididae), pp. 1-67 in Zootaxa 3864 (1) on page 51, DOI:10.11646/zootaxa.3864.1.1, http://zenodo.org/record/4930433